Aid reimagined: Results from an elite survey on perceptions of progress, capacity, and development cooperation - Ana Horigoshi; Samantha Custer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Development effectiveness is an ever-growing concern for development partners. Particularly in a world of increasing budget constraints and trade-offs, it is crucial for development partners to maximize the results of any development intervention. While the importance of a locally-led approach is well established, an essential step to achieve this objective has been neglected, reliable data on local perceptions. Seeking to fill this gap, this paper assesses the results of AidData's 2020 Listening to Leaders Survey looking into leaders' perceptions of progress against developmental goals, the perceived capacity constraints that may be hindering progress, and the potential role for international actors to support local actors in achieving their goals.
Keywords: C83; F63; O10; 330; elite survey; development cooperation; foreign assistance